The Influence of Teacher Competence on Student Learning Outcomes at SDN Donggobolo - Anis Mulyalana; Azra Fauzi; Jessy Parmawati Atmaja (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to examine the influence of teacher competence on student learning outcomes at SDN Donggobolo, a primary school located in a remote area with limited resources. A quantitative approach using a correlational survey method was employed. Data were collected through student perception questionnaires on teacher competence, which included four dimensions: pedagogical, professional, personal, and social, as well as academic reports in Indonesian Language and Mathematics subjects. The results showed that students’ perceptions of teacher competence were categorized as high, with average scores above 3.5 on a 4-point Likert scale. Student academic achievement was also high, with the majority falling into the “Excellent” and “Good” categories. Simple linear regression analysis revealed that 99.99% of the variance in student learning outcomes could be explained by their perception of teacher competence (R² = 0.9999; p < 0.00001). These findings indicate that teacher competence is a key factor in improving learning quality, even in resource-limited school settings. The impact of this study supports the development of teacher competency enhancement programs to sustainably improve student academic performance.